Long term mechanical properties of composite laminates - Ong, Chieh Sheng. (2013)
Carbon Fiber Reinforced Polymer (CFRP) are becoming increasing important in the aerospace industry due to its superior properties in areas such as strength to weight ratio compared to traditional materials such as aluminium. As such, research in this new generation of material is essential to ensure its’ usability and employability in the aerospace industry. The scope of the project is to carry out experimental research on the long term mechanical properties of L-930 satin woven CFRP. In this project, both tensile and shear specimens are being fabricated, experimented and analyzed upon. From the experimental research, several important mechanical properties such as shear and elastic modulus, maximum shear and tensile strength and poisson ratio etc are being investigated and analyzed. These experimental results will serves as a stepping stone to future research in CFRPs.